Dillinger [videorecording (DVD)] - Milius, John; Milius, John; Oates, Warren, 1928-1982; Johnson, Ben, 1918-1996; Phillips, Michelle, 1944-; Leachman, Cloris; Stanton, Harry Dean, 1926-2017 (MGM Home Entertainment, 2009)
Through all their outrageous escapades, the Dillinger gang maintained a certain mystique in the eyes of the American public. To a citizenry in the depths of the depression, the gang seemed almost like heroes, who enlivened their days with fabulous feats of crime. This film provides a glimpse of the lives of those involved in the most interesting crime saga in American history.